The Influence of Entrepreneurial Orientation and Brand Trust on Marketing Performance with Value Creation as a Mediating Variable in Creative SMEs in Bengkayang City - Cinda, Julianti; Hiong, Lauw Sun; Siam, Stivenes Tjin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine and understand how entrepreneurial orientation, brand trust, and value creation can influence marketing performance in Creative SMEs in Bengkayang City. This study uses a quantitative research method with a questionnaire as the data collection method, where the sample used in this research consists of 120 MSME owners/managers. The sampling technique in this study employs a stratified random sampling method. Data analysis was conducted using the SEM (Structural Equation Modeling) technique with AMOS version 26.0. The research results show that entrepreneurial orientation does not have a positive influence on the marketing performance of Creative MSMEs in Bengkayang City, followed by brand trust which has a positive influence on marketing performance, then entrepreneurial orientation and brand trust have a positive influence on value creation, and the final hypothesis is that value creation does not have a positive influence on marketing performance.